2014
DOI: 10.1007/s00253-014-5648-0
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of sludge from full-scale anaerobic digesters operated in municipal wastewater treatment plants

Abstract: This study applied Illumina high-throughput sequencing to explore the microbial communities and functions in anaerobic digestion sludge (ADS) from two wastewater treatment plants based on a metagenomic view. Taxonomic analysis using SILVA SSU database indicated that Proteobacteria (9.52-13.50 %), Bacteroidetes (7.18 %-10.65 %) and Firmicutes (7.53 %-9.46 %) were the most abundant phyla in the ADS. Differences of microbial communities between the two types of ADS were identified. Genera of Methanosaeta and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
97
3
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(119 citation statements)
references
References 54 publications
17
97
3
2
Order By: Relevance
“…Purple colours represent taxa with highest similarity to the mixotrophic genus Methanosarcina, and the blue bars are OTUs related to the obligatory acetotrophic Methanosaeta. Black bars represent relatives of Thermoplasmatales and the uncoloured bars denote OTUs with low sequence homology to previously characterised species Lee et al 2012;Sundberg et al 2013;Yang et al 2014). However, in comparison with our study, Sundberg et al (2013) reported a higher relative abundance of Firmicutes (14-38 %) and lower levels of Bacteroidetes (>22 %) and Proteobacteria (1-9 %) in their sewage sludge digesters, whereas Yang (2014) recorded lower levels of Bacteroidetes (7-10 %).…”
Section: Microbial Community Composition and Dynamics Linked To Increcontrasting
confidence: 82%
“…Purple colours represent taxa with highest similarity to the mixotrophic genus Methanosarcina, and the blue bars are OTUs related to the obligatory acetotrophic Methanosaeta. Black bars represent relatives of Thermoplasmatales and the uncoloured bars denote OTUs with low sequence homology to previously characterised species Lee et al 2012;Sundberg et al 2013;Yang et al 2014). However, in comparison with our study, Sundberg et al (2013) reported a higher relative abundance of Firmicutes (14-38 %) and lower levels of Bacteroidetes (>22 %) and Proteobacteria (1-9 %) in their sewage sludge digesters, whereas Yang (2014) recorded lower levels of Bacteroidetes (7-10 %).…”
Section: Microbial Community Composition and Dynamics Linked To Increcontrasting
confidence: 82%
“…Acetate was not detected in any of the sampled digesters (data not shown), consistent with the dominance of Methanosaetaceae and indicating that syntrophic acetoclastic methanogenesis in these reactors keeps pace with acetogenesis. A previous metagenomic study of the ST and SWH digesters similarly found the Methanosaeta to be dominant in all but one sample (49), suggesting this pattern is stable over time.…”
Section: Discussionmentioning
confidence: 83%
“…It may reflect small differences in operating conditions and feedstock composition between the digesters. As a metagenomic study of the ST and SWH digesters found that they did not significantly differ in genomically encoded metabolic functions (49), it may also be due to stochastic occupation by closely related and functionally interchangeable taxa of the limited set of biochemical niches within the anaerobic digestion process. A high level of functional redundancy is commonly reported in anaerobic digester communities (12).…”
Section: Discussionmentioning
confidence: 99%
“…The recently developed Illumina MiSeq platform can yield more detailed information of microbial community with greater throughput but less cost (Caporaso et al 2012;Nelson et al 2014). Illumina-based sequencing has found applications in characterizing the bacterial community in various natural and man-made environments, such as drinking water biofilter (Liao et al 2014), biofilm on drinking water distribution pipe (Wu et al 2014), anaerobic digestion sludge (Yang et al 2014), tropical rainforest leaf litter , river water (Staley et al 2013), soil (Rubin et al 2013), and mangrove wetland sediment (Jiang et al 2013). In addition, Illumina-based sequencing has also had several applications to characterize archaeal community in natural and man-made environments, such as fluid and sediment at a shallow marine hydrothermal site (Lentini et al 2014), biogas-producing and phenol-degrading bioreactor (Ju and Zhang 2014), and reservoir sediment (Zhang and Huang 2013).…”
Section: Introductionmentioning
confidence: 99%